SYSTEMATIC LITERATURE REVIEW: STUDENTS’ GENERIC SCIENCE SKILLS IN CHEMISTRY LEARNING - Nandari, Gita; Miterianifa, Miterianifa; Sari, Fahira Purnama; Trisnayanti, Yetty (Journal of Chemistry Education and Integration, 2025)
Science generic skills are part of the 21st-century skills. This has triggered massive innovation in science generic skills research especially, in chemistry subjects including in Indonesia. These skills contribute to an individual's practical participation and success in the surrounding environment. This research aims to analyze by literature study the trend of science generic research in Indonesia based on articles published in national and international journals. This qualitative research used a content analysis approach with a systematic literature review technique to analyze the research trends of science generic skills in chemistry subjects in Indonesia. Based on the predetermined inclusion criteria, 26 articles were collected for analysis using the Paper Classification Form (PCF) instrument. The research findings show the dominance on the topic of science generic skills research strategies in chemistry subjects conducted on various issues showing that learning strategies as much as 37%, dominate the improvement of generic skills in chemistry subjects, followed by teaching materials at 22%, learning models 18%, learning instruments 11%, and on the topic of learning evaluation being a minor topic as much as 4%, where the dominant dependent variable is related to science generic skills in chemistry learning.Keywords: Science Generic Skills, Chemistry Learning, and Systematic Literature Review